Improving the sustainability and durability of performance swimwear through consumer knowledge and usage habits - Upton, Bridget; James, Alana (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
As with any sport, the desire to progress in swimming by any means is unending. There are constant advancements being made in the textile technology of performance fabrics, with most technologic developments being focused on synthetic fabrics. Synthetic fibres, such as polyester can take from 20 up to 200 years to degrade and can release a range of chemicals having a detrimental effect on the planet (Uren, 2024). This paper explores performance swimwear’s environmental impact and proposes solutions for both industry and users. Key issues include the reliance on synthetic fibres, fabric deterioration, and insufficient consumer knowledge about reducing environmental impact and extending garment longevity. The study begins with a comprehensive literature review, which dissects the issues at hand and begins to deliberate possible solutions. Gaps in knowledge were identified and addressed through a series of qualitative interviews to gain first-hand insight from consumers and users of performance swimwear. The findings suggest that consumer knowledge around aftercare is insufficient. There is a lack of communication from brands on this subject, as well as a reluctancy from consumers to seek out this information. Thus, the common areas of wear and lack of knowledge on aftercare result in premature disposal of swimwear. The suggestion of designing for emotional durability presents a potential solution to increasing the longevity of swimwear. In addition to this, implementing upcycling schemes could reduce environmental impact and improvements in aftercare, such as improved communication and access to information is recommended.